Mechanics of Sister Chromatids studied with a Polymer Model - Zhang, Yang; Isbaner, Sebastian; Heermann, Dieter W. (Frontiers in Physics, 2013)
Sister chromatid cohesion denotes the phenomenon that sister chromatids are initially attached to each other in mitosis to guarantee the error-free distribution into the daughter cells. Cohesion is mediated by binding proteins and only resolved after mitotic chromosome condensation is completed. However, the amount of attachment points required to maintain sister chromatid cohesion while still allowing proper chromosome condensation is not known yet. Additionally the impact of cohesion on the mechanical properties of chromosomes also poses an interesting problem. In this work we study the conformational and mechanical properties of sister chromatids by means of computer simulations. We model both protein-mediated cohesion between sister chromatids and chromosome condensation with dynamic binding mechanism. We show in a phase diagram that only specific link concentrations lead to connected and fully condensed chromatids that do not intermingle with each other nor separate due to entropic forces. Furthermore we show that dynamic bonding between chromatids decrease the Young's modulus compared to non-bonded chromatids.